OPTIMASI AMOBILISASI UREASE DARI Schizzosaccharomyces pombe MENGGUNAKAN MATRIK KITOSAN-POLIETILEN GLIKOL - Dewi, Hastini Artha; Prasetyawan, Sasangka; Mahdi, Chanif (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
Schizosaccharomyces pombe is yeast that production urease and extraceluller enzyme. Urease can hydrolyze urea to be ammonia and carbondioxide. Free urease is unable to be reused, therefore urease is needed to immobilized in certain matrix. This research studies to determine optimum condition from chitosan concentration and enzyme concentration. Urease was immobilized by entrapment method using matrix chitosan-polyethylene glycol with make a variation to chitosan concentration (1.5; 2; 2.5; 3; 3.5) % (w/v) and make a variation to  urease concentration (0.840; 1.680; 2.520; 3.360; 4.200) mg/mL. Enzyme activity was defined as the amount of mikromol ammonia per minute, and resulted ammonia was analyzed by Nessler method. The results showed that the optimum condition of  immobilization uerase is achieved on chitosan concentration 3% (w/v) and urease concentration of  2.52 mg/mL and urease yielding in 2.36  mg/gram matrix chitosan-polyethylene glycol within the activity of  0.53 Units. Key words: activity, chitosan-polyethylene glycol, Schizosaccharomyces pombe, urease